Membrane sweeping at initiation of formal labor induction - a randomized controlled trial - Tan, P.C.; Jacob, R.; Omar, S.Z. (2006)
OBJECTIVE: To determine the benefit of membrane rate, reduced oxytocic drug use, shortened induction to sweeping at initiation of labor induction in conjunction delivery interval, and improved patient satisfaction. with formal methods of labor induction. METHODS: Two hundred seventy-four women at term with a singleton fetus in cephalic presentation and intact membranes were randomly assigned to receive membrane sweeping or no membrane sweeping at initiation of formal labor induction with either dinoprostone pessary or amniotomy. Outcome measures included mode of delivery, induction-to-delivery interval, dinosprostone dose, any oxytocin use and duration of oxytocin use in labor, visual analog score for pain associated with sweeping, and visual analog score for satisfaction with the birth process. RESULTS: Two hundred sixty-four women (136 sweep and 128 no sweep) had their data analyzed. Ten women (4 sweep and 6 no sweep) were excluded because of exclusion criteria infringements. Swept women had higher spontaneous vaginal delivery rate (69 compared with 56, P = .041), shorter induction to delivery interval (mean 14 compared with 19 hours, P = .003), fewer that required oxytocin use (46 compared with 59, P = .037), shorter duration of oxytocin infusion (mean 2.6 compared with 4.3 hours, P = .001) and improved visual analog score for birth process satisfaction (mean 4.0 compared with 4.7, P = .015). The reduction in dinoprostone dose used (mean 1.2 compared with 1.3, P = .082) was not significant. Postsweeping visual analog score for pain (mean 4.7 compared with 3.5, P < .001) was significantly increased. CONCLUSION: Membrane sweeping at initiation of labor induction increased the spontaneous vaginal delivery rate, reduced oxytocic drug use, shortened induction to delivery interval, and improved patient satisfaction.